Methane conversion into different hydrocarbons or oxygenates: current status and future perspectives in catalyst development and reactor operation. Issue 2 (20th December 2016) - Kondratenko, Evgenii V.; Peppel, Tim; Seeburg, Dominik; Kondratenko, Vita A.; Kalevaru, Narayana; Martin, Andreas; Wohlrab, Sebastian
Abstract : This Perspective highlights recent developments in methane conversion into different hydrocarbons and C1 -oxygenates. Our analysis identified possible directions for further research to bring the above approaches to a commercial level. Abstract : This Perspective highlights recent developments in methane conversion into different hydrocarbons and oxygenates (methanol, its derivatives, and formaldehyde) with the purpose to address the global demand for efficient and environmentally friendly production of these bulk chemicals. Our analysis identified possible directions for further research to bring the above approaches to a commercial level. As no progress in the development of catalysts for the oxidative coupling of methane could be identified, improvements are expected through reactor operation, cost- and energy-efficient methods for product separation and for providing pure oxygen. With respect to methane oxidation to methanol, further progress can also be achieved by proper catalyst design on the basis of fundamental knowledge especially gained from homogeneous and enzymatic catalysts as well as from theoretical calculations.